Information technology in crisis situations and civil protection – CROalertNet - Filipović, Antun Matija; Bralić, Vladimir; Bralić, Tina (Crisis Management Days, 2024)
The paper presents the developmental idea of the application and platform CROalertNet, which is aimed at improving the safety and awareness of the citizens of the Republic of Croatia through an innovative system for timely warning of various types of crises. Through the analysis of functionality, technological infrastructure, and user experience, it is shown how this platform can serve as a tool in the national protection and rescue system, providing key information in moments of crisis and promoting a culture of readiness and prevention among the population. By implementing the latest technological solutions and a community-based approach, CROalertNet contributes to society's resilience in responding to crises, making information accessible, understandable, and action-oriented for all users. A strong and scalable platform that uses cloud technology to ensure high availability and reliability of services is the foundation of the project. The platform uses advanced solutions for real-time data processing and analysis, ensuring the speed and accuracy of information. One of the important aspects of the application is also its focus on offline operation, and thanks to its modular design, the platform is ready for future expansions and integrations with other systems and technologies, such as artificial intelligence, to improve threat detection and personalize the user experience.